The isokinetic rotator cuff strength ratios in overhead athletes: Assessment and exercise effect - Berckmans, K.; Maenhout, A. G.; Matthijs, L.; Pieters, L.; Castelein, B.; Cools, A. M. (Physical Therapy in Sport, 2017)
Objective: Muscle strength imbalance in the shoulder region can be considered as a predisposing factor in the development of movement dysfunctions, possibly leading to overuse injuries. Repetitive overhead throwing, performed in sports, may result in muscle imbalance between the external (ER) and internal (IR) rotators. Muscle strength measured with an isokinetic device, is reported as a concentric (CON) or eccentric (ECC) force. The balance between an agonist and an antagonist is mentioned as a ratio (CON/ CON or ECC/CON). The aim of this systematic literature review is to provide an overview of the existing evidence considering the isokinetic muscle strength ratios of ER and IR of the shoulder in healthy overhead athletes. In addition, the effect of exercise programs on these ratios was investigated. Methods: Two online databases (Web of Science and PubMed) were consulted using different search strategies. Articles were selected based on inclusion and exclusion criteria. All included articles were assessed on their methodological quality. Results and conclusions: There is moderate evidence for a lower functional deceleration ratio (ECC ER/ CON IR) at the dominant side. This lower ratio is due to a large overweight of CON IR strength on that side. There is no consensus about which exercise program is the most effective in altering the shoulder isokinetic strength ratios.